(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The definition of social responsibility has often changed over the time. Differences in the economies of the United States of America (USA) and Europe have a strong impact on the social responsibility and stakeholders’ expectations from socially responsible business (SRB). The economic sector of the USA makes a significant contribution to addressing social and development initiatives in the local community, while in European countries there is an expectation that the state will meet such needs. The globalization processes transfer American corporate culture all around the world, as well as the engagement in solving social problems in the communities in which they operate. The economic model of social responsibility puts the profit motivation into the first place and emphasizes that it is the most effective tool for solving the world problems. The new circumstances in which businesses operate and the fact that information are available always and everywhere have a strong influence on the evolution of the social responsibility model from the economic to the socio-economic model. The role of business is not just to make profit, but also to cooperate between companies and society, and a balanced benefit for all stakeholders. This work consists of three parts. The introduction describes a traditional and new approach to social responsibility and benefits for companies that operate under the principles of social responsibility. The second chapter outlines European Union (EU) guidelines on SRB while concluding remarks synthesize the benefits of social responsibility in modern business as well as the critiques of the model. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.